Prevalence, antibiotic and heavy metal resistance of Vibrio spp. isolated from the clam Meretrix meretrix at different ages in Geligang, Liaohe estuary in China - Su, Jie; Zhang, Yingxue; Hu, Tian; Ming, Hongxia; Xie, Yuyang; Jin, Yuan; Shi, Tingting; Fan, Jingfeng (Frontiers in Marine Science, 2022)
Vibrio as one of the main pathogens of shellfish diseases can cause serious human seafoodborne gastroenteritis and even death. In this study, we analyzed the bacterial communities from the clam, and compared the resistance phenotypes and genotypes of Vibrio spp. from Meretrix meretrix at different growth stages. High-throughput sequencing analysis revealed the predominance of Proteobacteria (50%) in the bacterial community and Vibrio was one of the dominant genera in the clam hepatopancreas in the summer. Vibrio abundance in Meretrix meretrix positively correlated with the water temperature (p<0.05). A total of 73 Vibrio isolates from Meretrix meretrix were classified into 19 species and the dominant strains included V. mediterranei (19%) and V. harveyi (11%), V. algolyticus (10%), and V. parahaemolyticus (8%). The species and abundance of Vibrio spp. were the highest in the 3-year-old of Meretrix meretrix compared with clams of other ages in the summer. Among the 73 isolates, 68 Vibrio strains were resistant to other 15 antibiotics except for sulfamethoxazole-trimethoprim with 57 resistant phenotypes. The most prevalent resistance was toward clindamycin (76%), followed by amikacin (63%), ampicillin (62%), rifampicin (62%), vancomycin (57%), and amoxicillin (50%). The ARI values of Vibrio spp. in different ages ranged from 0.13 to 0.18, and ARI values of 3-year-old (ARI=0.18) clams are higher than that of other ages clam. Approximately 72% of the resistant isolates showed multidrug-resistant phenotypes with maximum resistance to 15 antibiotics. Tolerance to heavy metals including Cd, Zn, and Cu was detected in the majority of antibiotic resistant isolates. In addition to the co-resistance to the same class of antibiotics, resistance to cephalosporin (CFP, CEP, CZ) were significantly correlated with penicillins (AMP, AMC) (p< 0.01), tetracycline (p < 0.001), sulfanilamide (SXT) (p< 0.01) and quinolone (CIP) (p< 0.01). The heavy metal resistance genes copB and nccA were significantly correlated with the clindamycin resistance phenotype (p<0.01). This study revealed that the habitat of Meretrix meretrix is in low exposure to antibiotics, and a link between heavy metal resistance genes and antibiotic resistance.